Determinan Persepsi Etika Mahasiswa Akuntansi Dengan Love Of Money Sebagai Variabel Intervening (Studi Kasus Di Universitas Muhammadiyah Surakarta) - Kumala, Maruta Ratu, Dr.Fatchan Achyani, M,Si (2016)
The purpose of this study is to examine the effect of variables of gender and age toward variable of love of money and ethical perception. Besides that, this study is aimed to analyze the correlation between the class of love of money and ethical perception in accounting students. This study used survey as a method where the primary data obtainable from questionnaire. The population of this study is accounting students of Bachelor degree and Master of Accounting students in Muhammadiyah University of Surakarta that was done the course Etika Profesi and Bisnis Syariah. Total of sample is about 88 respondents. This study also used path analysis (analisis jalur) to analyze the hypothesis. The result of this study shown that (1) Gender is not influence to the love of money of accounting students, (2) Age isn't influence to the love of money of accounting students, (3) Love of money influence to the ethical perception of accounting students, (4) Gender isn't influence to the ethical perception of accounting students through love of money, (5) Age isn't influence to the ethical perception of accounting students through love of money.